Ailelerin Bitkisel Yağ Tüketimleri Üzerine Bir Araştırma: Samsun İli Örneği - Gündüz, Orhan; Esengün, Kemal (My University, 2010)
Bu araştırmada, Samsun ilinde yaşayan 150 aileden anketlerle elde edilen veriler kullanılarak bitkisel yağ tüketiminin değerlendirilmesi amaçlanmıştır. Aileler harcanabilir gelirlerine göre 5 gruba ayrılarak analizler yapılmıştır. İncelenen aileler ortalama 4 kişiden oluşmakta ve 1600TL/ay gelire sahiptir. Aileler, gelirlerinin yaklaşık %20’sini gıda harcamalarında kullanmaktadırlar. En düşük gelir grubunda yer alan aileler toplam gelirin %8’ini almakta iken, en yüksek gelir grubundakiler %38’ini almaktadırlar. Araştırma alanı için Gini katsayısı 0.29 olarak hesaplanmıştır. İncelenen ailelerde yıllık kişi başına bitkisel yağ tüketimi 18 kg’dır. Bu ailelerde en fazla ayçiçeği olmak üzere zeytinyağı ve mısır yağı tüketilmektedir. Tüketim tercihlerinde ürünün sağlıklı olması yanında fiyatı da önemli rol oynamaktadır. Aileler, ayçiçeği yağını çoğunlukla yemek yapmak için kullanırken, zeytinyağını salata yapmak için kullanmaktadır.

In the study was aimed to evaluate of vegetable oil consumption of 150 households in the Samsun province by using household food consumption survey data. The households were evaluated into the 5 groups compared with the income levels. Research results showed that the average households consisted of 4 individuals and average household income was 1600 TL month-1. Research results also showed that the households spend 20% of their total income on food. The households in the lowest income group had 8% of total income, while the households in the higher income group had 38%. Gini coefficient was estimated to be 0.29 for surveyed households. Annually vegetable oil consumption per capita was 18 kg in the sample households. The households‘ majority consumed the sunflower oil, olive oil and maize oil. Healthy and price of vegetable oil were important factors on the consumption choice for the households. Sunflower oil was used for cooking in the households, while olive oil was used for salad make
A research on the vegetable oil consumption of households: a case of Samsun province
Keywords: İktisat; İşletme